ELIMINATING DOMESTIC VIOLENCE FROM THE PERSPECTIVE OF THE PRINCIPLE OF BALANCE - Muhadar, Nemos (Awang Long Law Review, 2025)
This dissertation is entitled "The Elimination of Domestic Violence According to the Perspective of the Principle of Balance." Domestic violence (KDRT) fundamentally violates the goals of marriage—to form a happy, perpetual, and harmonious family—and constitutes a gross violation of human rights. Despite the existence of Law Number 23 of 2004 concerning the Elimination of Domestic Violence (UU PKDRT), the prevalence and complexity of domestic violence cases continue to rise, urging a philosophical and doctrinal re-evaluation of the current legal framework. This study addresses two pivotal legal issues: (1) the underlying philosophy of eliminating domestic violence from the perspective of the Principle of Balance, and (2) the necessary reformulation of the arrangement for eliminating domestic violence based on this principle. The research method is normative legal research using conceptual, statutory, case, and comparative approaches. The current UU PKDRT criminal sanctions are limited to imprisonment and fines. This limitation results in an imbalance, particularly when a victim (eg, a wife) seeks both justice for the abuse and the preservation of her family unit, a core objective explicitly stated in the Law. This study concludes that the Principle of Balance, rooted in monodualistic justice and aligned with Restorative Justice, necessitates the accommodation of alternative criminal sanctions (such as supervision or social work) for certain types of domestic violence. This reformulation is essential for bridging the gap between retributive punishment and the ultimate goal of maintaining a harmonious and prosperous household (ius constituendum).